Relationship between motor coordination, cognitive abilities, and academic achievement in Japanese children with neurodevelopmental disorders - Takuya Higashionna; Ryoichiro Iwanaga; Akiko Tokunaga; Akio Nakai; Koji Tanaka; Hideyuki Nakane; Goro Tanaka (SAGE Publishing, 2017)
Background/Objective: Motor coordination impairment is common in children with neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (AD/HD). The purpose of this study was to investigate the relationship between motor coordination, cognitive ability, and academic achievement in Japanese children with neurodevelopmental disorders. Methods: Thirty-four school-age (6-12 years old) children with neurodevelopmental disorders and 34 age-matched typically developing (TD) children were recruited in this study. Correlations between the scores of the Movement Assessment Battery for Children-2 (M-ABC2) and the Kaufman Assessment Battery for Children - Second Edition (K-ABCII) that assesses cognitive abilities, and academic achievement were analyzed. Results: The children with neurodevelopmental disorders obtained a lower total score and all component scores on M-ABC2 compared to the TD children. In children with neurodevelopmental disorders, M-ABC2 Manual Dexterity score was significantly correlated with K-ABCII Simultaneous Processing (r = .345, p = .046), Knowledge (r = .422, p = .013), Reading (r = .342, p = .048), Writing (r = .414, p = .017), and Arithmetic (r = .443, p = .009) scores. In addition, M-ABC2 Balance score was significantly correlated with K-ABCII Learning (r = .341, p = .048), Writing (r = .493, p = .004), and Arithmetic (r = .386, p = .024) scores. Conclusion: These findings stress that it is essential to accurately identify motor coordination impairments and the interventions that would consider motor coordination problems related to cognitive abilities and academic achievement in Japanese children with neurodevelopmental disorders.